Proximity of Teaching with Learning: A Case Study of an Accredited Institution (Research Journal on Multi-disciplinary Issues, 2026)
This study explores the proximity between teaching and learning processes at an accredited higher education institution in Madhesh Province, Nepal. Focusing on JS Murarka Multiple Campus, Lahan, Siraha, an accredited community campus affiliated with TU, the researcher investigates how the alignment (or lack thereof) between teaching strategies and students’ learning practices influences educational outcomes. Employing a case study approach, data were gathered through multiple sources: classroom observations using CCTV, interviews with 10 faculties, interviews with 20 first-year students from BBS and BEd, and an analysis of students’ academic records, covering both internal and final assessments. The findings reveal that despite the availability of adequate facilities to support teaching and learning, most faculty members continue to rely on traditional, teacher centered methods. These approaches tend to prioritize covering course content rather than responding to students’ preferred ways of learning. As a result, teaching and learning often move in different directions, leading to a noticeable gap or low proximity between the two. This misalignment has contributed to poor academic outcomes for students. The study underscores the need for teaching practices that are responsive to students’ learning processes, and recommends faculties need to align their teaching strategies with how students best engage with course materials.